Rendering theology with 2-year-old children: a Godly Play and grounded theory combination. Issue 2 (3rd April 2019) - Frady, Kathy
ABSTRACT: Research conducted with a specialized population such as very young children is fraught with issues not faced by research conducted with older participants. While researchers have conducted interviews with adults regarding their perceptions of young children and researchers have observed young children, this study was designed to allow 2-year-old children to be in a setting that offered the needed backdrop of language and play interaction in order capture theological understanding from the child's point of view. Using Godly Play with grounded theory allowed the emergence of the concept of rendering theology with 2-year-old children. The sub-themes included: Eager Receptiveness, Pretend to the Read the Bible Play, and Jesus Play. This study highlighted not only a theory regarding very young children's theological ideas, but also a spiritual qualitative methodology that may be used for future research with 2-year-old children.